The devil's art : divination and discipline in early modern Germany - Coy, Jason Philip, 1970- (Studies in early modern German history., 2020)
"The Devil's Art explores the Lutheran clergy's campaign to root out popular divination among their parishioners in the wake of the Reformation and why these efforts ultimately failed"--